Microwave-dried or air-dried? Consumers' stated preferences and attitudes for organic dried strawberries. A multi-country investigation in Europe. (June 2019) - Asioli, D.; Rocha, C.; Wongprawmas, R.; Popa, M.; Gogus, F.; Almli, V.L.
Abstract: Non-thermal food processing technologies are becoming more important in the organic food sector because, beyond preserving the organic feature, they could offer organic products with additional benefits in terms of enhanced nutritional content and healthiness as well as better sensory properties that could satisfy the more complex demands of organic consumers. Berries have a well-known health benefits and show increasing market shares in European markets while dehydration can increase the food convenience in terms of extended shelf-life. This study investigates for the first time organic consumers' stated preferences, attitudes and individual differences for a non-thermal organic processing technology. Specifically, we investigated consumers' preferences for organic dried strawberries varying in drying technology used, such as the most conventional (i.e. thermal) air drying and the most innovative (i.e. non-thermal) microwave drying, origin, price levels, and nutrient contents in three European countries: Norway, Romania and Turkey. Data from a total of 614 consumers were collected through an online choice experiment. Results show that on average consumers prefer organic dried strawberries produced with air drying technology that have national origin, with natural nutrient content and at low price, but country and individual differences are identified. Consumers who showed least rejection for microwave dried products are young, mostly from Norway and have higher positive attitudes towards new food technologies. Consumers who showed most rejection for microwave dried products are older, mostly from Turkey and have higher positive attitudes for organic, natural and ecological products. Organic producers who adopt microwave drying might better inform consumers about the characteristics, the process and highlight the nutritional benefits of such technology. Finally, this research informs policy makers about the need to define and regulate more clearly microwave drying as an organic technology, as well as to regulate labelling to ensure that consumers are not misled and correctly informed about the new technology. Graphical abstract: Unlabelled Image Highlights: First study to look at consumers' preferences for non-thermal processed (i.e. microwave drying) organic foods. Preferences for organic dried strawberries are investigated in three European countries. On average consumers reject microwave drying and prefer air drying. Producers should better inform consumers of the nutritional benefits of microwave drying.